(untitled) (Research, Society and Development, 2022)
The energy demand grows daily in the world and is heavily dependent on fossil fuels, the main emitters of gases that cause the greenhouse effect. Environmental impacts, such as global warming, have encouraged the development of alternative fuels, in which biofuels stand out, fuels obtained from the processing of biomass, a source of renewable and sustainable energy. Biodiesel is a biofuel produced by transesterification or cracking of triglycerides from oleaginous raw materials, the cracking product is called ecodiesel. Palm oil (“dendê”) is an oilseed that has high oil productivity, low cost and lack of seasonality, but its processing generates a large amount of solid waste that needs proper treatment. Thus, the objective of this work was to present a bibliographic review with a proposal for the production of ecodiesel from palm oil using gasification to treat solid waste, using the concepts of a biorefinery. A process flowchart was prepared based on a theoretical survey carried out in several scientific bases, such as SCIELO, Google Scholar and ScienceDirect and was developed in Lucid chart software. It was found that palm oil is promising in the production of ecodiesel and that thermo-conversion processes, such as gasification, can be used to add value to solid waste.